2022
DOI: 10.1177/0032258x211073003
|View full text |Cite
|
Sign up to set email alerts
|

Developments in UK police wellbeing: A review of blue light wellbeing frameworks

Abstract: Policing demands are widely acknowledged to negatively impact on the physical and mental health of police officers and staff. Research has documented the need for greater insight into the stressors and trauma that impact police officers, with a current national drive towards enhancing the police wellbeing agenda: namely, Oscar Kilo and the National Wellbeing Service. To understand the current wellbeing strategies in place, 34 Blue Light Wellbeing Frameworks were analysed. A mixed methods approach was adopted: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In order to address these questions there is need to address the problem of management apathy and resistance towards establishing mediators to prevent and mitigate not just trauma but the whole spectrum of police work related psychological wellbeing. According to Phythian, Birdsall, Kirby, Cooper, & Boulton (2022) trauma support should be delivered and in a holistic manner so that there is alignment between the physical and psychological (body mind and the soul) needs of the officers. There should also be personal and collective responsibility of maintaining health for example by exercising and other self-care activities that promote health.…”
Section: Discussionmentioning
confidence: 99%
“…In order to address these questions there is need to address the problem of management apathy and resistance towards establishing mediators to prevent and mitigate not just trauma but the whole spectrum of police work related psychological wellbeing. According to Phythian, Birdsall, Kirby, Cooper, & Boulton (2022) trauma support should be delivered and in a holistic manner so that there is alignment between the physical and psychological (body mind and the soul) needs of the officers. There should also be personal and collective responsibility of maintaining health for example by exercising and other self-care activities that promote health.…”
Section: Discussionmentioning
confidence: 99%
“…This research will assist organisational decision-making regarding focussing interventions on treating CF as opposed to merely increasing CS in police officers. It is evident organisations are making efforts to improve officers’ wellbeing through programmes such as the ‘Blue Light Wellbeing Framework’, which has elements of increasing CS (Phythian et al, 2022). The present study suggests boosting CS by attempting to improve resilience and educating officers on CF alone is not sufficient to alleviate its symptoms.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Mental illness in the workplace is a significant ‘economic burden’; it is estimated 16 million days are lost annually due to stress, anxiety, and depression (Office of National Statistics, 2020). Highly stressful occupations, such as police work, can negatively impact physical and mental health (Phythian et al, 2022). A study of 534 UK police officers revealed that 12% disclosed a mental health diagnosis and 26% suffered with mental illness (Jetelina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation